Morphology and properties evolution upon ring-opening polymerization during extrusion of cyclic butylene terephthalate and graphene-related-materials into thermally conductive nanocomposites. (April 2017) - Colonna, S.; Monticelli, O.; Gomez, J.; Saracco, G.; Fina, A.
Graphical abstract: Highlights: Ring-opening polymerization successfully used to produce thermally conductive nanocomposites. Infiltration of oligomers between nanoflakes is the key for their dispersion. Nanoflakes aspect ratio reduction demonstrated during polymerization in extruder. Thermal conductivity of nanocomposites decreases upon nanoflakes fragmentation. Large nanoflakes with low defectiveness are mandatory for high thermal conductivity. Abstract: In this work, the study of thermal conductivity before and after in-situ ring-opening polymerization of cyclic butylene terephthalate into poly (butylene terephthalate) in presence of graphene-related materials (GRM) is addressed, to gain insight in the modification of nanocomposites morphology upon polymerization. Five types of GRM were used: one type of graphite nanoplatelets, two different grades of reduced graphene oxide (rGO) and the same rGO grades after thermal annealing for 1 h at 1700 °C under vacuum to reduce their defectiveness. Polymerization of CBT into pCBT, morphology and nanoparticle organization were investigated by means of differential scanning calorimetry, electron microscopy and rheology. Electrical and thermal properties were investigated by means of volumetric resistivity and bulk thermal conductivity measurement. In particular, the reduction of nanoflake aspect ratio during ring-opening polymerization was found to have a detrimental effect on both electrical and thermal conductivities in nanocomposites.